A Feasibility Study Of Low-Power Laser Trepanning Drilling Of Composite Using Modified DVD Writer - Affandi , Nurfairuz Nadirah; Fikri Tamrin, Khairul; Azam Khan, Amir; Moghadasi, Kaveh; Mohamad Sharip , Mohd Ridzuan; Mohamaddan, Shahrol; Hossain, Anamul (International Journal of Integrated Engineering, 2020)
In the present study, laser cutting of cotton fiber composite laminate is experimented using a modified DVD writer drive. A 250 mW diode laser is initially extracted from a DVD writer drive, and then regulated by a custom-made laser driver circuit designed using a ProteusÂ® software. Experimental tests are carried out using multi-pass laser trepanning drilling at different drilling speeds and standoff distances (SODs). The cut quality is evaluated by measuring the extent of both oxide and resolidified resin regions. It was discovered that high speed of trepanning drilling and positive SOD significantly improve cut quality. Furthermore, positive and negative SODs require relatively high number of passes at different drilling speeds. From SEM micrographs, it is found out that the crack formation and fiber protruding happen in the drilling area due to thermal stresses and matrix vaporization.